Perceived Organizational Support in Mediating Organizational Climate and Workplace Conflict Against Workplace Deviant Behavior in Type D Hospitals in Konawe Kepulauan - Fridslan, Ulam; Anindita, Rina; Mustikawati, Intan Silviana (Green Publisher Indonesia, 2023)
The purpose of this study is to explain the effect of organizational climate and workplace conflict on workplace deviant behavior through perceived organizational support at Konawe Kepulauan General Hospital. Data collection using survey methods and online questionnaires. The population in this study were Type D Hospital employees in Southeast Sulawesi. Test the instrument for the validity of the questions and reliability as well as data analysis using the partial least squares - structural equation modeling (SEM) method. The results of this study show that there is a negative influence of organizational climate and a positive effect of workplace conflict on workplace deviant behavior. Organizational climate and workplace conflict are mediated by perceived organizational support for workplace deviant behavior. Suggestions from this study are that it is necessary to focus group discussions to create mutual trust, choose leaders who are capable in managing differences of opinion and monitor periodic evaluations.